Cooperative learning and embodied accountability: an ethnographic analysis of classroom participation in an English school - Laura Luna Figueroa (Arizona State University, 2015)
Based on a school ethnography carried out in an English primary school in the last years of New Labour Government,  this paper examines the processes and dynamics involved in the introduction of a cooperative learning method as part of the Success for All Literacy Program, which was being implemented in the school for the first time. It discusses the difficulties and resistances showed by children's interactions and teachers' declarations during the development of the program as the sign of competing agendas within the school and within the educational policy as well. They also manifest the deep penetration of a model of participation and learning that suits the neoliberal educational policy embraced by the British governments since the Education Reform Act in 1988 up to the present time.  The establishment of a culture of performativity and accountability is revealed in children's behavior during cooperative tasks as they tend to work in a competition rather than in a cooperation scheme and perceive their peers more as threats to their individual performance than as a support in their learning process. On the other side, teachers struggle to rely on a method more process-oriented than product-oriented as they feel that, with no individual and written tasks, they are not able to give account of children's progress and therefore, of their work as teachers.  The paper shows that a conception of learning (as private achievement), of person (as individual) and of classroom participation (as competition) are at play within the accountability educational system.